Peningkatan Kemampuan Matematika Permulaan Dengan Media Komputer Pada Anak Usia 5-6 Tahun Di TK Taman Harapan Bekasi - marjuki aljawi; Aditya Rahma Pambudi; Abdus Salam (STAI Publisistik Thawalib Jakarta, 2022)
This study aims to improve the initial mathematical ability with computer media in children aged 5-6 years. The method used is qualitative research through Classroom Action Research (CAR) with a spiral cycle model developed by Kemmis and Mc. Taggart. Data collection techniques were carried out using direct observation instrument sheets, field notes and documentation. The instrument was carried out in each cycle to determine the increase in initial mathematical abilities in children aged 5-6 years through computer media. Research shows that there is an increase in initial mathematical ability in children aged 5-6 years through computer media, namely in the pre-study the percentage is 43%, the first cycle is 65%, and the second cycle is 89%. The results in cycle II have exceeded the target to be achieved by the researchers, which is 70%. The results of improving early mathematical abilities in children aged 5-6 years through computer media in group B of Taman Harapan Bekasi Kindergarten can be said to be successful.